A solution to the Lifely Disobedience and its Effect to Stop Divorce - الدكتور محمد طعمھ القضاة (College of Education for Women, 2019)
Allah legislated marriage and made it dwelling, fellowship and mercy between the two couples, Prophet Moh'd (peace of Allah and blessing be upon him) ordered a husband to look after his wife, treat her with full charity and make love with here every kindly. On the other hand, he ordered a wife to obey her husband and respect him deeply, nevertheless, some obstacles may sometimes be appeared within the life of their marriage, this may be caused by either a husband or a wife. This problem is called lifely disobedience (AL-Noshooz). In the other words, this means that a wife begins to hate her husband, refuse his orders and not obey him. In brief, they hate each other which leads to some marks appear in their manners and bahaviours, for example, a wife refuses her husband's requests, orders and commands and so does the husband, he begins to leave her in bed and ignore her in treatment. The researcher explained a solution to the problem of disobedience after he had mentioned the types of it that might be appeared in the manners or behaviours of both a wife or a husband. This clear solution comes from the holy Quran, Prophet's tradition (Hadith) and Muslim Scientists, points of view, the researcher also mentioned how a husband may do towards manipulating this problem according to the instructions of Holly Quran and the Islam teaching first, a husband is ordered to advise his wife about the dangers of divorce and reminds her about Allah's punishment in the day of judgment. Then the researcher mentioned the second step which a husband may follow to avoid divorcing as ignoring her in bed. This step seems to be more serious than the previous one. After the researcher had explained everything about how to solve this problem in these previous steps according to the Holy Quran, Prophets Traditions and Muslim Scientists gradually, He mentioned the third step which is hitting the husband should avoid hitting his disobedient wife on her face, sensitive areas and infront of people, hitting wives shouldn't be more than ten flippings or whipping. The fourth step of solving the problem of disobedience is judging. Two persons judged between the two couples after hearing their complaints and the reason of this problem. One person belongs to a husband's family and the other belongs to a wif's family or relatives. Finally, the researcher mentioned the husband's lifely disobedience, it's limitations, treatment, conclusion, and the most important results